Doṣas by the Numbers: Buddhist Contributions to the Origins of the Tridoṣa-theory in Early Indian Medical Literature with Comparisons to Early Greek Theories of the Humours - Zysk, Kenneth G. (History of Science in South Asia)

(untitled) (University of Alberta Library, 2021)
This paper explores the origins of the Indian medical nosology involving the three doṣas from the perspective of its formulation into three or four distinct types. The essay compares similarities in passages from three different literary sources: Pāļi texts of early Buddhism, early Sanskrit medical literature, and Greek texts from the Hippocratic Corpus and the Anonymus Londiniensis. The study reveals that the tridoṣa-theory, common to āyurvedic literature from an early time was based on the adoption and then adaption of ideas nourished by an intellectual exchange with the Greek-speaking world.